Estrategia didáctica "INTELINGÜIS" y su influencia en el desarrollo de la Inteligencia Lingüística en niños y niñas de cinco años de la Institución Educativa inicial Nº 288 del distrito de Rioja. - Torres Trigozo, Sheena (2008)
The present investigation has aimed at applying didactic strategy INTELINGÜIS to lift the linguistic- intelligence level in the five - years boys and girls of the Institution Educativa Nº 00288 of Rioja city. study justifies itself for his relevance in the country educational specifically in Communication integral’s area that develops in the initial- education level and to have permitted to stimulate in the boys and girls linguistic abilities so level phonetic - phonological, lexical - semantic and grammatical syntactic having as scientific bases to the following foundations: Sociological, biological, psychological and pedagogic. Apoyados in the basics mentioned, they carne into question them hypothesis following: Alternative Hypothesis: lf he applies didactic strategy INTELINGÜ\S, then will have influence significantly in the linguistic- intelligence level of the five – years boys and girls of her Institution Educativa Inicial N° 00288. Void Hypothesis: lf he applies didactic strategy INTELINGÜIS, then will not have influence in the linguistic intelligence level of the five - years boys and girls of her Institution Educativa Inicial N° 00288. He shows it was shaped for 25 little girls and 05- years children elderly of the section her Ardillitas I.E. N. He applied himself at the end of this period the behind test stop determining the manufactured changes for the didactic strategy INTELINGÜ\S in the linguistic- intelligence levels of the boys and girls. After analysis and interpretation of the results, demonstrate that the strategy, didactic INTELINGÜIS is elevate the average of intelligence linguistic of 12 obtained in pre test (profit in process) to 17 obtained is pos test ( outstanding profit) of the experimental group. Also, contrastation estadistic of hypothesis wit a level of significance of 0.05 and one tabulate of -1,67 with 58 gl, gives like result a calculated of -21,36, begun which accepts hypothesis alternating tesis and hypothesis is rejected null thesis.